Bayesian Statistics

The Buhlmann Model

Setting up the notation

$X_{ij}$ is the $j^{th}$ claim from the $i^{th}$ risk

$\bar{X_{i}}$ is the average claim from the $i^{th}$ risk

$m(\theta) = E(X_{ij}|\theta)$ is a random variable as $\theta$ is a random variable

$s^2(\theta)=Var(X_{ij}|\theta)$ is also a r.v.




Defining problem

Postulate that $m(\theta)=a_0 + a_1 X_1 + a_2 X_2 + ...+a_nX_n$

and so try and find the values of $a_0, a_1,...,a_n$ which give us the best estimate of $m(\theta)$

Calculation of $a_0$

We wish to minimise $f=E\left[(m(\theta)-a_0 + a_1 X_1 + a_2 X_2 + ...+a_nX_n)^2\right]$

Calculate$ \frac{\partial f}{\partial a_0}=E\left[2(m(\theta)-a_0 + a_1 X_1 + a_2 X_2 + ...+a_nX_n)(-1)\right]$

and set to zero to find the maximum

$E\left[2(m(\theta)-a_0 + a_1 X_1 + a_2 X_2 + ...+a_nX_n)(-1)\right]=0$

$2 E(m(\theta)) - 2a_0 - 2a_1E(X_1)-...-2a_nE(X_n)=0$

Then as the expectation is taken over the random variable $\theta$ and each of the $X_1,...,X_n$ are taken from the same distribution for given $\theta$ then $E(X_j)=\mu$ and so:

$a_0=\mu\left(1-\displaystyle\sum_{j=1}^{n}a_j \right)$

Interim results

Result 1: $E(X_jX_k)=\nu^2+\mu^2$


First apply the Tower Law


Then the standard result $E(XY)$

$E(X_jX_k)=E\left[Cov(X_j, X_k|\theta) + E(X_j|\theta).E(X_k|\theta)\right]$

$E(X_jX_k)=E\left[Cov(X_j, X_k|\theta) + m(\theta).m(\theta)\right]$

$E(X_jX_k)=E\left[Cov(X_j, X_k|\theta)\right] + E(m^2(\theta))$

As $X_j$ and $X_k$ are conditionally independent - the first term is zero

Then the defn of variance, applied to the second term gives

$E(X_jX_k)=Var(m(\theta)) + \left[E(m(\theta))\right]^2$



Result 2: $E(X_k^2)=\sigma^2 + \nu^2+\mu^2$


First apply the Tower Law




$E(X_k^2)=\sigma^2 + \nu^2+\mu^2$


Result 3: $E(X_k m(\theta))=\nu^2+\mu^2$


First apply the Tower Law

$E(X_k m(\theta))=E(E(X_k m(\theta)|\theta))$

then $m(\theta|\theta)$ is a constant so:

$E(X_k m(\theta))=E(m(\theta).E(X_k|\theta))$

$E(X_k m(\theta))=E(m^2(\theta))$

$E(X_k m(\theta))=\nu^2+\mu^2$


Calculation of $a_k$

Back to $f=E\left[(m(\theta)-a_0 + a_1 X_1 + a_2 X_2 + ...+a_nX_n)^2\right]$

Calculate$ \frac{\partial f}{\partial a_k}=-E\left[2(m(\theta)-a_0 + a_1 X_1 + a_2 X_2 + ...+a_nX_n)(X_k)\right]$

And solve $\frac{\partial f}{\partial a_k}=0$

$E(m(\theta)X_k)-E(a_0X_k)-E(a_kX_kX_k)-E\left[\displaystyle\sum_{j=1,j\neq k}^{n}a_j X_j X_k \right]=0$

$\nu^2+\mu^2-a_0\mu-a_k(\sigma^2 + \nu^2+\mu^2)-\displaystyle\sum_{j=1,j\neq k}^{n}a_j (\nu^2+\mu^2) =0$

After much re-arrangement this becomes

$a_k=\frac{\nu^2}{\sigma^2+n \nu^2}$

Finishing off the proof

So we have: $a_0=\mu\left(1-\displaystyle\sum_{j=1}^{n}a_j \right)$ and $a_k=\frac{\nu^2}{\sigma^2+n \nu^2}$

The best estimate is $m(\theta)=a_0 + \displaystyle\sum_{j=1}^{n}a_j X_j$


$m(\theta)=(1-Z)\mu + Z.\bar{X}$ where $Z=\frac{n\nu^2}{\sigma^2+n\nu^2}$